2009
DOI: 10.1021/jp907216g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall, Water-Soluble Magnetite Nanoparticles with High Relaxivity for Magnetic Resonance Imaging

Abstract: Ultrasmall (3, 4, 5, and 6 nm), water-soluble Fe3O4 magnetic nanoparticles were synthesized in diethylene glycol (DEG) via a facile one-pot reaction. Hydrodynamic size and relaxation time measurements did not show particle aggregation when Fe3O4 nanoparticles were dispersed in phosphate buffered saline, fetal bovine serum, or calf bovine serum for 1 week. Furthermore, the new Fe3O4 nanoparticles tolerated high salt concentrations (≤1 M NaCl) and a wide pH range from 5 to 11. Surface modification of the nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 42 publications
7
99
1
Order By: Relevance
“…Up to now, many methods have been developed to prepare Fe 3 O 4 nanocrystals with small sizes on the nanometer scale, which include hydrothermal synthesis [9,10], chemical coprecipitation [11-13], and thermal decomposition and/or reduction [14,15]. Besides these nanosized particles, the secondary structural superparamagnetic Fe 3 O 4 particles have also attracted increasing attention due to their practical applications in magnetic separation and magnetic-targeted substrate delivery [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, many methods have been developed to prepare Fe 3 O 4 nanocrystals with small sizes on the nanometer scale, which include hydrothermal synthesis [9,10], chemical coprecipitation [11-13], and thermal decomposition and/or reduction [14,15]. Besides these nanosized particles, the secondary structural superparamagnetic Fe 3 O 4 particles have also attracted increasing attention due to their practical applications in magnetic separation and magnetic-targeted substrate delivery [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Accelerating proton relaxation underlies the function of contrast agents used in magnetic resonance imaging (MRI). 1936 Thus, a better elucidation of the mechanism of action of Gd(III)-carbon nanomaterials may provide an opportunity to increase the sensitivity of Gd(III) agents beyond what is currently accessible by Gd(III)-complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Parekh et al synthesized magnetite nano-fluid and reported that the thermal conductivity of fluid decreases linearly with increase in temperature [20]. Hu et al prepared magnetite nanocrystals via facile onepot reaction method and reported that the magnetite nanocrystals are good magnetic resonance agents for invivo and in-vitro applications [21]. Darken et al discussed in detail about the thermodynamics of the ironoxide system [22].…”
Section: Introductionmentioning
confidence: 99%